Analysis of Civics Teachers' Strategies in Developing Moral Intelligence to Create a Moral Generation in Public Junior High Schools in Muaro Jambi Regency - Heri Usmanto; Dona Sariani; Zainal Arifin; Amir Syariffudin; Reka Sepriani (Civics Education and Social Science Journal (CESSJ), 2026)
This research aims to analyze the strategies of Civic Education (PPKn) teachers in developing moral intelligence to shape a morally upright generation in public junior high schools across Muaro Jambi Regency. The subjects of this study include PPKn teachers, students, and principals as additional informants. This study employed a qualitative method with a phenomenological approach. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that PPKn teachers have integrated moral values into learning through habituation, discussions, case studies, creative media use, and linking lessons to students’ daily lives. The strategies applied include fostering positive behavior, collaborative learning, and consistent teacher role-modeling in instilling Pancasila values. These results highlight the central role of PPKn teachers in shaping students’ character, thereby fostering a generation with morality and integrity. The study recommends continuous innovation in digital-based learning methods and strengthening the capacity of PPKn teachers as moral role models in schools. References Bego, K. C. (2016). Peran Guru Pendidikan Kewarganegaraan Dalam Membentuk Karakter Siswa dan Implikasinya Terhadap Ketahanan Siswa. Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 5(3), 235 240. https://doi.org/10.33366/JISIP.V5I3.306. Dewi Sadiah, Metode Penelitian Dakwah Pendekatan Kualitatif dan Kuantitatif (Bandung: PT. Remaja Rosdakarya, 2015), h. 88. Latifah, H. (2017). Profesi Keguruan Menjadi Guru Profesional. Yogyakarta: Pustaka Baru Press. Lexy. J. Moleong, Metodologi Penelitian Kualitatif, (Bandung: PT Remaja Rosdakarya, 2000), hlm. 3 Nanang Fatchurochman, Teaching with Love: Pendekatan Cinta dan Akhlak Mulia dalam Pembelajaran, (Jakarta: Senama Sejahtera Utama, 2008), hal. 102 Sudarwan Danim, Menjadi Peneliti Kualitatif Rancangan Metodologi, Presentasi, dan Publikasi Hasil Penelitian untuk Mahasiswa dan Penelitian Pemula Bidang Ilmu Sosial, Pendidikan, dan Humaniora, (Bandung: Remaja Rosdakarya, 2002), Cet. I, hlm. 51. Sugiyono, Metode Penelitian Pendidikan; Pendekatan Kuantitatif dan Kualitatif dan R&D , (Bandung: Alfabeta, 2006), hlm. 310 Sugioyono, Memahami Penelitian Kualitatif, (Bandung: Alfabeta,2005), h. 82 Suharsimi Arikunto, Prosedur Penelitian Suatu Pendekatan Praktek, (Jakarta : PT. Rineka Cipta, 2002, Cet.XII), hlm.149 Suprahatiningrum, J. (2017). Guru Profesional: Pedoman Kinerja, Kualifikasi & Kompetensi Guru. Yogyakarta: Ar-Ruzz Media